1983
DOI: 10.1111/j.0954-6820.1983.tb03757.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic and Metabolic Effects of Timolol (Blocadren®) on Ischaemic Myocardium

Abstract: The effects of timolol (2.5 mg i.v.) on coronary haemodynamics and myocardial metabolism were studied in 26 patients with angina pectoris. Cardiac venous flow (CVF) was measured by thermodilution technique. Blood was sampled for metabolic studies. Angina pectoris was induced by atrial pacing and the same heart rate was regained after timolol. Metabolic ischaemia was defined as reduction in myocardial lactate extraction ratio (MLE) by at least 50% and to a ratio below 0.15. The study was completed in 22 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

1986
1986
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 21 publications
0
4
0
2
Order By: Relevance
“…Similarly, in patients with angina pectoris, beta-blockade does not reduce myocardial oxygen demand or ischemia if angina is induced by atrial pacing (41).…”
Section: Myocardial Ischemiamentioning
confidence: 99%
“…Similarly, in patients with angina pectoris, beta-blockade does not reduce myocardial oxygen demand or ischemia if angina is induced by atrial pacing (41).…”
Section: Myocardial Ischemiamentioning
confidence: 99%
“…By reducing peripheral lipolysis, this pharmacological class lowers the levels of FFA in the blood and allows a change in the heart's energy metabolism that increases the use of carbohydrates [36]. Through these metabolic processes, betablockers are responsible for this substrate competition's decreased myocardial FFA uptake and increased glucose utilization [37,38]. A decrease in FFA delivery and an increase in the availability of arterial glutamate, which is highly advantageous for myocardial tissue as it can serve as both aerobic and anaerobic fuel, making it a particularly versatile substrate [38], are both likely to be responsible for the increase in carbohydrate metabolism in the heart that was observed after a beta-blockade [39,40].…”
Section: Betablockersmentioning
confidence: 99%
“…Data from previous studies have shown that in 26 patients with angina pectoris, timolol (2.5 mg i.v) did not reduce myocardial oxygen demand or ischemia if angina is induced by atrial pacing [58]. In addition, Heidland et al [59] retrospectively analyzed 106 patients who underwent 2 coronary angiography procedures within 6 months, and demonstrated that the use of b-blockers was negatively correlated with plaque disruption [59].…”
Section: B-blockersmentioning
confidence: 99%